Assessment of Angiography-Based Renal Quantitative Flow Ratio Measurement in Patients with Atherosclerotic Renal Artery Stenosis - Xiang Huang; Xiao-Lan Li; Heng Zhou; Xiao-Mei Li (Cardiovascular Therapeutics)
Background. Quantitative flow ratio (QFR) is an angiography-based fractional flow reserve measurement without pressure wire or induction of hyperemia. A recent innovation that uses combined geometrical data and hemodynamic boundary conditions to measure QFR from a single angiographic view has shown the potential to measure QFR of the renal artery-renal QFR (rQFR). Objective. The aim of this pilot study was to assess the feasibility of rQFR measurement and the contribution of rQFR in selecting patients with atherosclerotic renal artery stenosis (ARAS) undergoing revascularization. Methods. This retrospective trial enrolled patients who had ARAS (50-90%) and hypertension. The enrolled patients were treated by optimal antihypertensive medication or revascularization, respectively, and the therapeutic strategies were based on rFFR measurement and/or clinical feature. Results. A total of 55 patients underwent rQFR measurement. Among the enrolled patients, 18 underwent optimal antihypertensive medication and 37 underwent revascularization, 19 patients in whom rQFR and rFFR were both assessed. During the 180-day follow-up, 25 patients saw an improvement in their blood pressure among the 37 patients that underwent revascularization. ROC analysis revealed that rQFR had a high diagnostic accuracy for predicting blood pressure improvement (AUCrQFR=0.932, 95% CI 0.798-0.998). The ideal cut-off value of rQFR for predicting blood pressure improvement after revascularization is ≤0.72 (sensitivity: 72.00%, specificity: 100%). The paired t test and Bland–Altman analyses demonstrated good agreement between rQFR and rFFR (t=1.887, 95% CI -0.021 to 0.001, 95% limits of agreement: -0.035 to 0.055, p=0.075). The Spearman correlation test reveals that there was a significant positive correlation between rQFR and rFFR (r=0.952, 95% CI 0.874 to 0.982, p<0.001). Conclusion. The rQFR has the potential to enhance the ability of angiography to detect functionally significant renal artery stenosis during angiography and to produce results that are comparable to invasive hemodynamic assessment.